A qualitative study of the causes and circumstances of drowning in Uganda - Anthony Buyinza Mugeere; Frederick Oporia; Olive Kobusingye (BMC, 2022)
Abstract Background Drowning is a serious worldwide and preventable injury problem, especially in low- and middle-income countries (LMICs). The aim of this paper is to draw on the results of semi-structured interviews with witnesses, family members and friends of persons involved in fatal and nonfatal drowning incidents to describe the circumstances of drowning in both lakeside and non-lakeside districts and to identify potential contextually appropriate interventions for drowning prevention and surveillance in Uganda. Methods The findings presented in this study were based on data collected from study participants selected through purposive sampling comprising 324 individual face-to-face interviews with drowning witnesses, family members, friends of and survivors of drowning and ten (10) focus group discussions held with community members in 14 districts in Uganda. Data analysis was done using the Framework Analysis Approach with the aid of the Microsoft Atlas ti software (version 8) program. Results The study results reveal a range of circumstances under which drowning occurs in Uganda, poor record keeping of drowning incidents, fear of reporting drowning incidences to the authorities, challenges in preventing drowning and proposed strategies for mitigating the problem. Conclusions This study found that there is no specialized record keeping system for drowning cases in Uganda and where such records are kept, the system is entirely manual (in hard copy form) with no electronic storage of data. Secondly, the drowning cases reported to police posts and stations in various parts of the country are not transmitted to the district headquarters and national database. These and other conclusions not only provide valuable insights into understanding of drowning circumstances but also the key policy and programme interventions for water-based economic activities such as fishing and public water transportation in Uganda and other LMICs.